Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Albert Watkins at the gravesites of his oldest brother Amos Watkins and his wife Rosa Langston Watkins. Chattanooga Memorial Park